2021
DOI: 10.3390/nu13124547
|View full text |Cite
|
Sign up to set email alerts
|

Ergogenic Effects of Green Tea Combined with Isolated Soy Protein on Increasing Muscle Mass and Exercise Performance in Resistance-Trained Mice

Abstract: It is well known that supplementation with high protein after exercise can effectively promote muscle synthesis and repair, while green tea is rich in catechins that have antioxidant effects. We aimed to explore the effects of green tea combined with isolated soy protein on increase muscle mass in resistance-trained mice. A total of 32 male ICR mice (8-weeks old) were divided into four groups (n = 8/group), sedentary control group (SC), isolated soy protein with green tea group (ISPG), resistance training grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 35 publications
(39 reference statements)
0
8
0
Order By: Relevance
“…Meanwhile, muscular glycogen and glucose turned into pyruvate, and then the overproduced pyruvate conversed into LA, leading to the deposition of LA and metabolic acidosis (Johnson & Bagby, 1988; Shi et al., 2019). Furthermore, exhaustive exercise can enhance the catabolism of body protein, resulting in excessive production of urea nitrogen (Lee et al., 2021). Therefore, the body's exercise endurance decreases, ultimately leading to fatigue.…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, muscular glycogen and glucose turned into pyruvate, and then the overproduced pyruvate conversed into LA, leading to the deposition of LA and metabolic acidosis (Johnson & Bagby, 1988; Shi et al., 2019). Furthermore, exhaustive exercise can enhance the catabolism of body protein, resulting in excessive production of urea nitrogen (Lee et al., 2021). Therefore, the body's exercise endurance decreases, ultimately leading to fatigue.…”
Section: Discussionmentioning
confidence: 99%
“…Animal studies have demonstrated that soy protein or soy protein isolate ingestion stimulate muscle protein synthesis by activating the mTOR pathway and inhibiting FOXO transcription factors [ 35 , 36 , 37 ]. This protein anabolic effect was more pronounced in studies treated simultaneously with other nutrients or supplements, such as chromium, green tea, and leucine, thus indicating a synergic effect [ 38 , 39 ]. In addition, several RCTs have demonstrated that soy protein supplementation has a protective effect on muscle.…”
Section: Discussionmentioning
confidence: 99%
“…The weight-loading started at 5% of body weight and increased by 25% of body weight weekly until the final weight was 100% body weight, as we previously described. In resistance training, the climbing routines involved 4 repetitions/set and 3 sets/day with 1 min rest between sets ( 28 ). The equipment was set under 5 cm of water to provide negative stimulation and increase climbing motivation.…”
Section: Methodsmentioning
confidence: 99%